PENINGKATAN HASIL BELAJAR PENJUMLAHAN PECAHAN BERPENYEBUT TIDAK SAMA DENGAN PENDEKATAN PMR DI SEKOLAH DASAR - Herman, Depi Yuliadi; Zainil, Melva; Arlis, Syamsu (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective of this study is to describe the improvement of the learning results of adding fractions with different denominators using Pendidikan Matematika Realistik approach on the 5th grade students of SDN 08 Campago Ipuh Kota Bukittinggi. This study is a classroom action research, and employs qualitative and quantitative approaches. The research object is the 5th grade students of SDN 08 Campago Ipuh Kota Bukittinggi. The results showed several improvements, including: a) the implementation of the lesson plan in cycle I has an average score of 87.5% (Very Good), while the average score for cycle II is 92.86% (Very Good); b) the teaching stages (the teacher’s activity) has an average score of 76.6% (Good) in Cycle I, while the average score in cycle II is 93.75%(Very Good); c) The learning implementation (the student’s activity) has an averge score of 76.6% (Good) in cycle I, and it increase to 93.75% (Very Good) in Cycle II; d) the learning results has an average score of 66.59 (Fair) in Cycle I and it increase to 86.17 (Very Good) in Cycle II. This study concludes that the implementation of Pendidikan Matematika Realistik approach significantly improves the learning results of adding fractions with different denominatorsof the 5th grade students in SDN 08 Campago Ipuh Kota Bukittinggi.Keywords: adding fractions with different denominators, Pendidikan Matematika Realistik approach